(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
The purpose of this paper is to present the profile of scientific production on babassu coconut breakers in national postgraduate studies. At first, the coconut breakers are portrayed as extractivist women who have a strong relationship with their traditional territory. It is characterised as a basic, descriptive, mixed and documentary study. The results discuss the characteristics of the research on coconut breakers, with emphasis on postgraduate programmes, lines of research, location and subject matter. It concludes that scientific production on the quebradeiras is an attractive topic, explored by various areas of knowledge.